Preference toward future mode of delivery: how do antepartum preferences and prior delivery experience contribute?*. (6th October 2014) - Sparks, Teresa N.; Yeaton-Massey, Amanda; Granados, Jesus M.; Handler, Stephanie J.; Meyer, Michelle R.; Caughey, Aaron B.
Abstract: Objective : Examine postpartum preferences toward future mode of delivery (MOD), considering recent MOD, antepartum preferences, and demographics. Study design : Prospective cohort study where a survey was distributed in outpatient obstetrics clinics to pregnant women over 18 years at 28 weeks gestation or later. Surveys gathered demographics, obstetric history, and preference toward vaginal delivery (VD) versus cesarean delivery (CD). Women were again surveyed at 6–8 weeks postpartum. Chi-square test compared proportions, and logistic regression controlled for potential confounders. Results : A total of 299 women returned postpartum surveys and expressed preferences. Comparing women who experienced VD versus CD, the majority who had a VD (92.1%) would choose this again, while only 1.9% preferred CD. Among the CD group, preferences were mixed: 29.4% desired repeat CD, 34.1% preferred VD, and 36.5% were undecided ( p  < 0.001). Adjusted odds were 34.4 (95% CI 9.4–126.1) for preferring VD over CD among women who experienced a recent VD, adjusting for parity, age, ethnicity, education, possible depression, and type of provider. Conclusions : The majority of women preferred VD postpartum. Of the minority who desired CD, antenatal preference for cesarean and prior experience with CD were important factors. This highlights the impact of individual desires and experience, and underscores importance of antenatal counseling.